Association study between multiple system atrophy and TREM2 p.R47H. (August 2018) - Ogaki, Kotaro; Heckman, Michael G.; Koga, Shunsuke; Martens, Yuka A.; Labbé, Catherine; Lorenzo-Betancor, Oswaldo; Walton, Ronald L.; Soto, Alexandra I.; Vargas, Emily R.; Fujioka, Shinsuke; Uitti, Ryan J.; van Gerpen, Jay A.; et al.
Abstract : Objective: The triggering receptor expressed on myeloid cells 2 (TREM2) p.R47H substitution (rs75932628) is a risk factor for Alzheimer disease (AD) but has not been well studied in relation to the risk of multiple system atrophy (MSA); the aim of this study was to evaluate the association between the TREM2 p.R47H variant and the risk of MSA. Methods: A total of 168 patients with pathologically confirmed MSA, 89 patients with clinically diagnosed MSA, and 1, 695 controls were included. TREM2 p.R47H was genotyped and assessed for association with MSA. Positive results in the Taqman genotyping assay were confirmed by Sanger sequencing. The primary comparison involved patients with pathologically confirmed MSA and controls due to the definitive MSA diagnosis in the pathologically confirmed series. Results: We identified TREM2 p.R47H in 3 patients with pathologically confirmed MSA (1.79%), 1 patient with clinically diagnosed MSA (1.12%), and 7 controls (0.41%). Minimal AD pathology was observed for the pathologically confirmed MSA p.R47H carriers. For the primary comparison of patients with pathologically confirmed MSA and controls, risk of disease was significantly higher for p.R47H carriers (odds ratio [OR]: 4.39, p = 0.033). When supplementing the 168 pathologically confirmed patients with the 89 clinically diagnosed and examining the combined MSA series, the association with TREM2 p.R47H remained significant (OR: 3.81, p = 0.034). Conclusions: Our preliminary results suggest that the TREM2 p.R47H substitution may be a risk factor for MSA, implying a link to neuroinflammatory processes, especially microglial activation. Validation of this finding will be important, given our relatively small sample size; meta-analytic approaches will be needed to better define the role of this variant in MSA.